Shift Media Online Da’wah Innovation Diffusion in The Hijrah Youth Movement Community - Fita Faturokhmah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
This article discusses the experience the Hijrah Youth Movement Community adopts towards the innovation of online da’wah youtube. This research uses constructionism and phenomenological methods using Everett Rogers’ innovation diffusion theory. In-depth interview techniques, observations, and documentation are used for data gathering. Data analysis with statement meaning, meaning themes, General Description of the “essence” of the experiences. This study showed that the Hijrah Youth Movement Community conducted online da’wah with lectures on youtube and adopted shift media innovations. The audience knows youtube Youth Hijrah Shift Media through persuasive communication of managers and social media Instagram Shift Media. The decision to adopt youtube innovation Youth Hijrah Shift Media. Implement youtube Pemuda Hijrah Shift Media since first knowing the existence of youtube Pemuda Hijrah Shift Media. Confirmation of the innovation of the Hijrah Shift Media Youth Movement is satisfied. The Hijrah Youth Movement Community adopted the innovation of online da’wah youtube Youth Hijrah Shift Media because it has conformity and provides relative advantages to the Hijrah Youth Community